Preparation And Characterization Of Grafted Lignin Polyepoxide As A Fluid Loss Additive For Water-Based Mud - Taleb, Fayyadh Faisal Saleh (2015)
Soda lignin (SL) was extracted from oil palm empty fruit bunch (OPEFB) fiber as a natural biopolymer resource via soda pulping process.